Study of maternal and fetal outcome in pregnancy beyond 40 weeks: a prospective observational study at a tertiary institute - Kori, Shreedevi; Biradar, Dayanand; Biradar, Aruna; Yaliwal, Rajasri; Mudanur, Subhashchandra R.; Patil, Neelamma; Pujeri, Shivakumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Prolonged pregnancy is one that exceeds 42 0/7weeks. Management of prolonged pregnancy is very challenging in modern obstetrics. Methods: It is prospective observational study in department of Obstetrics and Gynecology, Shri B.M Patil medical college and Research center, deemed to be University, Vijayapur, North karnataka. Study period was from January 2018 to January 2019. Results: Total of 186 pregnant women were included in the study. Results in terms of age, gravidity, gestational age, time of induction, mode of delivery, neonatal outcome and maternal complications. Conclusion: Pregnancies beyond 40 weeks require early detection, effective fetal monitoring and proper planning of labour. In pregnancies beyond 40 weeks, decision of induction should be taken cautiously as early induction leads to failure of induction and increased rates of lower (uterine) segment Caesarean section (LSCS), while delayed induction leads to increased fetal complications.